Newborn hearing screening: Present scenario - Vishwambhar Singh (Wolters Kluwer Medknow Publications, 2015)
In 2009 many countries of the world met to discuss newborn and infant hearing screening current issues and guiding principles for action under World Health Organization (WHO) banner, though most of the countries who had begun this work as universal program or high risk screen do not have exact data and protocol. The developing countries also decided to become part of it and common guideline was proposed. India being part of it included hearing screening as one of the 30 diseases to be screened under Rashtriya Bal Swasthya Karyakram (RBSK). This article discusses all these issues of newborn hearing screening in the world and India.